SARS-CoV-2 hijacks neutralizing dimeric IgA for nasal infection and injury in Syrian hamsters1 - Biao Zhou; Runhong Zhou; Jasper Fuk-Woo Chan; Jianwei Zeng; Qi Zhang; Shuofeng Yuan; Li Liu; Rémy Robinot; Sisi Shan; Na Liu; Jiwan Ge; Hugo Yat-Hei Kwong; et al. (Emerging Microbes and Infections)
Prevention of robust severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection in nasal turbinate (NT) requires in vivo evaluation of IgA neutralizing antibodies. Here, we report the efficacy of receptor binding domain (RBD)-specific monomeric B8-mIgA1 and B8-mIgA2, and dimeric B8-dIgA1, B8-dIgA2 and TH335-dIgA1 against intranasal SARS-CoV-2 challenge in Syrian hamsters. These antibodies exhibited comparable neutralization potency against authentic virus by competing with human angiotensin converting enzyme-2 (ACE2) receptor for RBD binding. While reducing viral loads in lungs significantly, prophylactic intranasal B8-dIgA unexpectedly led to high amount of infectious viruses and extended damage in NT compared to controls. Mechanistically, B8-dIgA failed to inhibit SARS-CoV-2 cell-to-cell transmission, but was hijacked by the virus through dendritic cell-mediated trans-infection of NT epithelia leading to robust nasal infection. Cryo-EM further revealed B8 as a class II antibody binding trimeric RBDs in 3-up or 2-up/1-down conformation. Neutralizing dIgA, therefore, may engage an unexpected mode of SARS-CoV-2 nasal infection and injury.